2021
DOI: 10.1002/mgg3.1742
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cataract: An ocular manifestation of classical homocystinuria

Abstract: Background Homocystinuria is an autosomal recessive metabolic disorder occurring due to the defects in cystathionine‐β‐synthase enzyme. The study was carried out to investigate a Pakistani family presenting bilateral congenital cataract with symptoms of classical homocystinuria at LRBT Free Eye Hospital, Lahore, Pakistan. Methods Three affected individuals of the family presented skeletal deformations, intellectual disability, speech delay, and myopia with bilateral congenital cataract. Genetic analysis on DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Regarding patients with monogenetic methylation disorders, studies on patients with MTHFR 20 and CBS deficiency 21,22 reported ectopia lentis, congenital cataract, 23 and myopia as commonly observed ophthalmological features. One patient with CBS in our cohort showed ectopia lentis, while it was not reported for any patient affected by MTHFR.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding patients with monogenetic methylation disorders, studies on patients with MTHFR 20 and CBS deficiency 21,22 reported ectopia lentis, congenital cataract, 23 and myopia as commonly observed ophthalmological features. One patient with CBS in our cohort showed ectopia lentis, while it was not reported for any patient affected by MTHFR.…”
Section: Discussionmentioning
confidence: 99%
“…Only nine patients were identified with homocystinuria, and none had c.833T>C mutation [ 22 ]. A study on three patients in a Pakistani consanguineous family with symptoms in 2021 confirmed homocystinuria was not detected with c.833T>C mutation [ 23 ]. Although the prevalence of c.833T>C is likely less among the Asian population, but it is the most prevalent mutation worldwide in the CBS gene related to homocystinuria, thus, it is important to find out the presence and prevalence of this mutation in Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%